Vehicle traffic differentiation and scheduling in sensor network using Ns2 - Ramalingam, Mritha; Puviarasi, R. (Academic Publications Ltd., 2018)
In this paper, the obligatory QoS administration stream parameters are characterized for every kind of activity as per now is the right time criticality and deferral affectability. The IEEE 802.15.4 is broadly utilized cutting edge standard convention as a part of numerous applications using remote sensor systems (WSNs) particularly in vehicular sensor systems (VSNs).In this paper, different planning calculations, for example, first in first out(FIFO), Priority line, Weighted Round Robin (WRR) and Deficit Weighted Round Robin(DWRR) are coordinated in consistence with IEEE 802.15.4 to enhance the throughput, upgrade the transmission capacity use rate and perform quick preparing and conveyance for dire information activity, we isolate the standard movement into different sorts of information on the premise of various QoS prerequisites. The required QoS administration stream parameters are characterized for every kind of movement as indicated by now is the ideal time criticality and postponement affectability.